Correlation regression and path-coefficient analysis of biochemical parameters associated with duration of crop growth in grape (Vitis vinifera) - GIRIDHARAN, M P; JINDAL, P C (The Indian Journal of Agricultural Sciences, 2013)
Genetic variability, correlation and direct and indirect effects of biochemical parameters associated with cropduration was studied in 15 genetically diverse genotypes of grape [Vitis vinifera L.) during 1991-94. The genotypesshowed significant variation for total phenols, total sugars, organic acids, total free amino acids, soluble protein, totalnitrogen peroxidases and polyphenol oxidase activity (ali in leaves) and total duration of the crop (from pruning toberry ripening). It indicated that the magnitude of variability for all the parameters are very high. The total free aminoacids in the leaves was found closely correlated with duration of crop growth and contributed significantly to thevariation in the duration of crop growth. Heritability and genetic advance were high for total free amino acids in theleaves.